2023
DOI: 10.7150/ijbs.87964
|View full text |Cite
|
Sign up to set email alerts
|

Targeting HMGB1: A Potential Therapeutic Strategy for Chronic Kidney Disease

Tongtong Liu,
Qian Li,
Qi Jin
et al.

Abstract: High-mobility group protein box 1 (HMGB1) is a member of a highly conserved high-mobility group protein present in all cell types. HMGB1 plays multiple roles both inside and outside the cell, depending on its subcellular localization, context, and post-translational modifications. HMGB1 is also associated with the progression of various diseases. Particularly, HMGB1 plays a critical role in CKD progression and prognosis. HMGB1 participates in multiple key events in CKD progression by activating downstream sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 169 publications
0
7
0
Order By: Relevance
“…Additionally, an interesting finding of our study was that the positive correlation between serum HMGB1 and the duration of diabetes may indicate that serum HMGB1 plays a significant role in the underlying mechanisms of diabetes-induced renal disease. As previously discussed, HMGB1 may play a more indispensable role in chronic diseases than in acute lesions ( 20 ), although extracellular HMGB1 levels can change at the moment of injury. A preclinical study also found that in the early stage after unilateral ureteral obstruction, renal tubular HMGB1 deletion had no obvious effect on renal injury, but it can significantly reduce renal interstitial fibrosis in the late/subacute stage ( 42 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Additionally, an interesting finding of our study was that the positive correlation between serum HMGB1 and the duration of diabetes may indicate that serum HMGB1 plays a significant role in the underlying mechanisms of diabetes-induced renal disease. As previously discussed, HMGB1 may play a more indispensable role in chronic diseases than in acute lesions ( 20 ), although extracellular HMGB1 levels can change at the moment of injury. A preclinical study also found that in the early stage after unilateral ureteral obstruction, renal tubular HMGB1 deletion had no obvious effect on renal injury, but it can significantly reduce renal interstitial fibrosis in the late/subacute stage ( 42 ).…”
Section: Discussionmentioning
confidence: 94%
“…High mobility group box 1 (HMGB1), as an important pro-inflammatory factor, has been found to be elevated in many metabolic and immune diseases, including sepsis ( 17 ), rheumatoid arthritis ( 18 ), and Alzheimer’s disease ( 19 ), and significantly correlated with their progression and prognosis. We recently noticed that HMGB1 activation in kidney disease promotes multiple key events in CKD progression by activating downstream signals, including kidney inflammation, development of persistent fibrosis, kidney aging, acute kidney injury to CKD transition, and important cardiovascular complications ( 20 ). Several clinical studies have also shown that elevation of the HMGB1 level is significantly correlated with kidney disease progression ( 21 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Upon its release, HMGB1 interacts with various receptors, notably the Receptor for Advanced Glycation End products (RAGE) and TLR4, which subsequently triggers podocyte apoptosis and promotes epithelial-mesenchymal transition (EMT)—processes that compromise podocyte integrity and function ( 23 , 24 ). Therapeutic strategies that interrupt the HMGB1-receptor signaling axis have demonstrated potential in ameliorating podocyte injury, consequently enhancing the integrity of the glomerular filtration barrier ( 25 ). This avenue represents a promising therapeutic target for ameliorating the progression of CKD ( Figure 1 ).…”
Section: Immunological Mechanisms In Podocytementioning
confidence: 99%
“…Ferroptosis is a form of programmed cell death that was first discovered in 2012 (Dixon et al 2012 ). The essence of ferroptosis lies in the depletion of glutathione, the decrease in the activity of glutathione peroxidase 4 (GPX4), and the inability of lipid peroxides to be metabolized through the GPX4-catalyzed glutathione reductase reaction (Liu et al 2023a , b ). Subsequently, the oxidation of Fe2 + leads to the generation of reactive oxygen species (ROS), thereby promoting the occurrence of ferroptosis (Galy et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…HMGB1 is a non-histone chromosomasal binding protein that exists in the nucleus of eukaryotic cells. Research has shown its involvement in the pathological processes of various diseases, including tumors (Tang et al 2023 ), chronic kidney disease (Liu et al 2023a , b ), autoimmune diseases (Ren et al 2023 ), and cardiovascular diseases (Zheng et al 2023 ). In the context of hematological malignancies, HMGB1 plays a pivotal role in modulating diverse biological processes, including cellular autophagy, differentiation, growth, immunity, and chemotherapy resistance (Yuan et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%